Clan Crypts on the Lower Don of the Early Catacomb Time and Genesis Issues of the Catacomb Rite - Alexey V. Kiyashko (Нижневолжский археологический вестник)
The article provides comprehensive information about two Middle Bronze Age burials (No. 26, 42) from the kurgan 1 in the burial mound Vesely I near Novocherkassk in the Rostov region. The burials contained double tombs with a complex rite and prestigious accompanying items namely bronze tools and silver jewelry. The analysis of the rite and the inventory of the considered catacombs as well as the stratigraphic data allowed identifying their cultural affiliation and attributing them to two successive stages of the Early Catacomb period on the Lower Don: pre-Donetsk (No. 26) and early Donetsk (No. 42) cultures. The presence of the crypt ritual signs in the first catacomb has become the important discovery. The ritual consists of skulls posthumous displacement at a significant distance from the backbone and probable additional reburial in an existing burial chamber. In the second catacomb dating back to a later period, the collapse of the skull on the chest of the buried individual was identified as unintentional and must have been associated with the skeleton soft tissues decomposition. A combined method for radiocarbon dating using accelerator mass spectrometry (AMS), DNA analysis of the bones as well as the isotope study of the teeth were carried out in the laboratories of Belfast and Harvard. It was established that all the buried individuals were close relatives in the male line. Furthermore, two brothers turned out to be buried in different catacombs No. 26 and 42 at different time. This degree of relationship of the buried allowed clarifying and correcting the radiocarbon dating of their remains. Firstly, the cross-overlap of the dates of close relatives made it possible to cut off the plumes of values related to the error of the method. Secondly, it has become possible to narrow the date range to the interval from the late 30th to the late 29th centuries BC considering the actual age of the brothers buried in different graves (excluding possible freshwater reservoir effect). Taking into account that the studied catacombs were related to different archeological periods, the data indicate an accelerated pace of cultural genesis in the early stages of catacomb culture compared to its developed or later periods.